The Analysis of Social Services Supervision of Beggars, Vagrants, And Abandoned People (PGOT): A Case Study of The “Silver Man” Phenomenon - Yusuf, Yusuf; Chuluk, Nisa Amelia; Jannah, Ghina Roudhotul; Khumayah, Siti; Rahmayanti, Rahmayanti (Jurnal Polisci, 2025)
Background. The presence of “Silver Man” has spread widely in several cities in Indonesia, including Cirebon. Their existence began in early 2021 after the pandemic era. The “Silver Man” phenomenon refers to individuals who paint their bodies silver or gray and beg in public spaces. Aims. This study aims to analyze the oversight conducted by the Cirebon City Social Services Department in response to the “Silver Man” phenomenon. Methods. The study employs a qualitative method with a case study approach, where data is collected through observation, interviews, and research documentation. Result. The results of the study indicate that the supervision and control measures implemented by the Social Affairs Department and the City Police of Cirebon are deemed ineffective and misdirected, as many beggars, vagrants, and homeless individuals (PGOT), including “Silver Man,” are not initially from Cirebon City, and the local government has established no follow-up policies. Efforts undertaken by the local government through the Social Affairs Department of Cirebon City, in collaboration with the Civil Service Police Unit (Satpol PP), continue to conduct routine PGOT enforcement in Cirebon City, as well as weekly Saturday outreach activities for street children in collaboration with volunteers based at Dukuh Semar street, Cirebon City. Conclusion. Community participation and strengthened policies by the local government are crucial to enhancing the effectiveness of monitoring the “Silver Man” phenomenon.